The magnitude of legal wildlife trade and implications for species survival - Marshall, Benjamin Michael; Alamshah, Aubrey L.; Cardoso, Pedro; Cassey, Phillip; Chekunov, Sebastian; Eskew, Evan A.; Fukushima, Caroline S.; Garcia-Diaz, Pablo; Gore, Meredith L.; Lockwood, Julie L.; Rhyne, Andrew L.; Sinclair, James S.; et al. (National Academy of Sciences, 2025)
The unsustainable use of wildlife is a primary driver of global biodiversity loss. No comprehensive global dataset exists on what species are in trade, their geographic origins, and trade's ultimate impacts, which limits our ability to sustainably manage trade. The United States is one of the world's largest importers of wildlife, with trade data compiled in the US Law Enforcement Management Information System (LEMIS). The LEMIS provides the most comprehensive publicly accessible wildlife trade database of non- the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) listed species. In total, 21,097 species and over 2.85 billion individuals were traded over the past 22 y (2000- 2022). When LEMIS data are combined with CITES records, the United States imported over 29,445 wild species, including over 50% of all globally described species in some taxonomic groups. For most taxa, around half of the individuals are declared as sourced from the wild. Although the LEMIS provides the only means to assess trade volumes for many taxa, without any associated data on most wild populations, it is impossible to assess the impact on biodiversity, sustainability of trade, or any potential risk of pest or pathogen spread. These insights underscore the considerable underestimation of trade and the urgent need for other countries to adopt similar mechanisms to accurately record trade.